Haploid biotechnology as a tool for creating a selection material for sugar beets - E. O. Kolesnikova; E. I. Donskikh; R. V. Berdnikov (Вавиловский журнал генетики и селекции, 2022)
Since the discovery of the phenomenon of haploidy, biotechnology has become an integral part in the successful creation of new varieties and hybrids of various plant species. In particular, these technologies are actively used in agriculture, which is concerned with increasing the volume and improving the quality of products. The integration of haploid production techniques together with other available biotechnological tools such as marker selection (MAS), induced mutagenesis and genetic engineering technologies can significantly accelerate crop breeding. This article shows the main stages in the development of biotechnology since 1921. Now they are successfully used to create doubled haploids to accelerate the selection process of various plants and, in particular, sugar beet, which is the most important sugar crop in regions with a temperate climate. There are several methods for obtaining forms with a single set of chromosomes. For sugar beets, the use of gynogenesis turned out to be expedient, since in this case the other methods turned out to be ineffective in the mass production of haploids. The article considers the stages of obtaining the H and DH lines of Beta vulgaris L., as well as the main stages of biotechnological production of homozygous breeding material of this culture. These stages include selecting parental forms – donor explants, sterilizing buds and introducing non-pollinated ovules in vitro, obtaining haploids, doubling their chromosome set, creating doubled haploids, determining ploidy at different stages, relocating the obtained plants to greenhouses and growing stecklings. A number of advantages that the technology of creating doubled haploids in vitro has in comparison with traditional methods of selection are described. It has been shown that the use of these approaches is relevant when obtaining new highly productive hybrids and varieties of agricultural plants; however, the methods for the production of homozygous forms in sugar beet still require additional research aimed at increasing the efficiency and reproducibility of each stage of the process.